Turnover in an Accounting Firm - Lane, Julia; Parkin, Michael (Journal of Labor Economics, 1998)
We use a unique data set to investigate whether a matching model can describe turnover in an accounting firm. The main focus of the article is to determine whether the probability of separation from employment varies in the way described by Jovanovic. The evidence suggests that as tenure increases both terminations and quits follow the predicted pattern.